PENGARUH MODEL PEMBELAJARAN PROBLEM SOLVING BERBANTUAN APLIKASI AUTOGRAPH TERHADAP KEMAMPUAN REPRESENTASI MATEMATIS SISWA KELAS VIII UPTD SMP NEGERI 1 PEMATANGSIANTAR - Br Ujung, Elisabet Pebrina; Tambunan, Lois Oinike; Simarmata, Gayus (Universitas Islam Sumatera Utara, 2025)
This study aims to examine the effect of the Autograph application-assisted Problem Solving learning model on the mathematical representation abilities of students in Grade VIII at UPTD SMP Negeri 1 Pematangsiantar. This study uses a quantitative experimental research design. Quantitative research is objective in terms of data collection, quantitative data analysis, and testing using statistical methods. This study will be conducted in class VIII of SMP Negeri 1 Pematangsiantar. The sampling technique used by the researcher to determine the sample in this study is cluster random sampling. Based on the results of data analysis and discussion, it can be concluded that there is a positive and significant effect of the use of the problem-solving learning model on the mathematical representation abilities of students in class VIII UPTD SMP Negeri 1 Pematangsiantar. This effect is shown by the correlation value between variables (R) of 0.945 and the regression equation ?̂ = −4.357 + 0.473? with a value of ? = 0.473. Based on the t-test results, it was found that there was a significant effect and the coefficient of determination showed a positive effect of 89.3%.